Morphogenetic and structural characteristics of Megathyrsus maximus cv. Centenário under defoliation intensities (Research, Society and Development, 2020)
The effect of defoliation intensities (20, 30, 40 and 50 cm above soil level) on green dry matter (GDM) yield and morphogenetic and structural characteristics of Megathyrsus maximus cv. Centenário were evaluated under field conditions in Roraima´s savannas. The effects of defoliation intensities on the GDM yields, leaf area index and leaf elongation rates was adjusted to the quadratic regression model and maximum values recorded with cutting at 35.8; 44.9 and 30.2 cm above soil level, respectively. The tiller population density, number of leaves tiller-1 and leaf appearance rate was inversely proportional to the intensity of defoliation, while the opposite occurred for to average leaf length and leaf senescence rate. Apical meristem removal percentage was higher with increasing defoliation intensity. Vigor regrowth showed close negative correlation with defoliation intensity level. Pastures of M. maximus cv. Centenário managed under 30 to 35 cm residue provides higher forage productivity, larger efficiency of forage utilization, greater tissue renewal and canopy structure more favorable to grazing.